1999
DOI: 10.1074/jbc.274.16.11159
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coordination between Initiation of HIV (+)-Strand DNA Synthesis and Primer Removal

Abstract: In this study, we have analyzed the interdependence between the polymerase and RNase H active sites of human immunodeficiency virus-1 reverse transcriptase (RT) using an in vitro system that closely mimics the initiation of (؉)-strand DNA synthesis. Time course experiments show that RT pauses after addition of the 12th DNA residue, and at this stage the RNase H activity starts to cleave the RNA primer from newly synthesized DNA. Comparison of cleavage profiles obtained with 3-and 5-end-labeled primer strands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 37 publications
7
53
0
Order By: Relevance
“…Mutant enzymes were generated through site-directed mutagenesis using the Stratagene Quick-change kit according to the manufacturer's protocol. Substrates used in this study were derived from the HIV-1 polypurine tract (PPT) as described in our previous studies (24,25): 5Ј-TTAAAAGAAAAGGGGGGA (PPT-1/18D); 5Ј-TTA-AAAGAAAAGGGGGG (PPT-1/17D); and 5Ј-ACTGGAAGGGCTGAT-TCA (PPT-2/18D). The model template used in this study provides complementarity to these primers: 5Ј-CGTTGTCAGTGAATCAGCC-CTTCCAGTCCCCCCTTTTCTTTTAAAAAGTGGCAAGA.…”
Section: Methodsmentioning
confidence: 99%
“…Mutant enzymes were generated through site-directed mutagenesis using the Stratagene Quick-change kit according to the manufacturer's protocol. Substrates used in this study were derived from the HIV-1 polypurine tract (PPT) as described in our previous studies (24,25): 5Ј-TTAAAAGAAAAGGGGGGA (PPT-1/18D); 5Ј-TTA-AAAGAAAAGGGGGG (PPT-1/17D); and 5Ј-ACTGGAAGGGCTGAT-TCA (PPT-2/18D). The model template used in this study provides complementarity to these primers: 5Ј-CGTTGTCAGTGAATCAGCC-CTTCCAGTCCCCCCTTTTCTTTTAAAAAGTGGCAAGA.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that this was observed only beyond the addition of 18 nucleotides, which corresponds to the distance between the polymerase and RNase H active sites of RT, suggests that both active sites need to be in contact with the DNA part of the primer/template hybrid substrate to favor the polymerase binding orientation. On the other hand, we cannot exclude the possibility that the RNA PPT sequence gets cleaved only after addition of the 18th DNA residue, instead of the 12th as previously demonstrated (32). If this were indeed the case, following the cleavage of the RNA PPT at the RNA⅐DNA junction by the RNase H activity of RT, the primer would serve as a de facto DNA primer.…”
Section: Discussionmentioning
confidence: 93%
“…As observed here and previously, the RNA PPT primer extended by 12 deoxyribonucleotides is still acting like the pure RNA PPT in terms of sensitivity to NNRTIs and NNTIs suggesting that the RNA PPT sequence is still part of the primer/template substrate. In previous work it was shown that RT pauses after the addition of the 12th DNA residue during the initiation of the (ϩ)-strand synthesis from the RNA PPT primer causing the cleavage of the PPT sequence at the RNA PPT-DNA junction (32). One hypothesis that could explain this discrepancy might be that the pausing of RT after the addition of 12 nt, which leads to the cleavage at the RNA PPT-DNA junction, occurs only during ongoing polymerization and not when using a pre-synthesized chimeric primer.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently studied the interplay between both active sites under saturating dNTP concentrations and demonstrated that a specific pausing site at position ϩ12 correlated precisely with the emergence of RNase H cleavage at the RNA-DNA junction that removes the RNA primer from newly synthesized DNA (23). In the present study, we have investigated the impact of diminished and biased dNTP pools on efficiency and accuracy of the polymerization process and the consequences regarding the interdependence between the two active sites of RT.…”
mentioning
confidence: 99%
“…During this process, a purinerich fragment near the 3Ј-end of the genomic RNA, i.e. polypurine tract (PPT), remains resistant to RNase H degradation and serves as a primer for (ϩ)-strand DNA synthesis (21)(22)(23)(24). Following its selection, the PPT primer is initially extended, and specific RNase H cleavage at the RNA-DNA junction removes the RNA fragment from newly synthesized DNA.…”
mentioning
confidence: 99%